Internal Audit Effectiveness in Oman’s Public Sector: A Cross Sectional Study - Al Abri, Fatma (2016)
Abstract Internal auditing is an indispensable component of corporate governance in both public and private organisations. It is designed to add value and enhance organisational operations by providing independent, objective assurance and consulting activities which assist in achieving organisational objectives. Despite the growing importance of internal audit function, few studies have focused on determinants of internal audit effectiveness in the public sector. Thus, this research investigates the factors that impact internal audit effectiveness in the Omani public sector. Previous studies used different measures of internal audit effectiveness; this research utilized the perceptions of managers’ audited departments to evaluate effectiveness and test whether there is an interrelationship between internal audit effectiveness and six factors: internal auditors’ competence, size of internal audit department, relationship between internal and external auditors, top management support for internal audit functions, independence of internal audit department, and providing value-added services. Data was collected through two independently administered surveys, one of targeted managers of audited departments and a second of targeted internal auditors. A sample size of 209 observations from 31 Omani public sector organisations was used to test the associations developed in the model. The Weighted Least Square multiple regression examined the relationship between internal audit effectiveness and six factors. The results indicate that size of internal audit department affects the effectiveness inversely, while independence affects it positively. Knowledge the determinants of internal audit effectiveness in the public sector will help internal auditing departments to meet their roles and responsibilities. The findings of this study will open new avenues for further research into internal audit in general, particularly with regard to public sector organisations.